A new path of sustainable development in traditional agricultural areas from the perspective of open innovation: A coupling and coordination study on the agricultural industry and the tourism industry - Peilei Qiu; Zhaoxing Zhou; Dong-Joo Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Background/Objective: The Chinese government is actively developing the rural economy and promoting the poverty alleviation campaign. The economic development of the traditional agricultural areas is essential to people's basic livelihood and social stability. The tourism industry has been proven to be an effective approach to promote the regional economy. It has become a hot issue as to how to develop the tourism industry in rural areas. Methods/Statistical Analysis: Based on a corresponding index system, a coupling coordination model was established to explore the coupling and coordination development of the agricultural industry and the tourism industry in Henan province, a traditional agricultural area in China. Findings: The result revealed that although the coupling degree between the agricultural and the tourism industry from the year of 2009 to 2018 is relatively stable, the coordination degree shows a continuous rising trend from 0.278 to 0.921. This indicated that the agricultural industry and the tourism industry in Henan province continues to interact with and influence each other, and the comprehensive development level and the coordination degree of the two industries have been constantly improved. Implications: From the result, it can be seen that the integration development of the agricultural industry and the tourism industry could be a new path to develop the economy of rural areas. From the perspective of sustainable development, suggestions are proposed to optimize the agricultural industrial structure, extend tourism industry chain and construct support policy to develop a sustainable mode of the agricultural industry and the tourism industry.
Keywords: 650; open innovation; coupling coordination; industrial integration; sustainable development; the agricultural industry; the tourism industry